Perspectives of knowledge about violence against migrant women: mapping academic production Strictu Sensu (Research, Society and Development, 2020)
Objective: To analyze the nature and trend of knowledge in Brazilian theses and dissertations on the theme of gender violence against immigrant and refugee women. Method: Inventory bibliographic research of an inventory nature that considered the theses and dissertations registered in the Bank of Theses of the Catalog of Theses and Dissertations of the Coordination for the Improvement of Higher Education Personnel. The search was in January 2020, 160 studies were retrieved and 14 (two theses and twelve dissertations) were selected for analysis. Results: There was growth in academic production. As for nature, there was a greater socio-cultural representation (8), followed by politics (3), clinical-epidemiological (2) and existential (1). As for the trend, there was a predominance of protective order (9), followed by assistance (4) and promotion (1). The studies showed violence in physical, sexual, domestic, obstetric, gender, structural, bullying, political persecution, restriction of human rights, family and social disruptions, racism, discrimination and prejudice. Conclusion: There was an absence of research conducted by professional nurses on the subject, constituting possible gaps in knowledge and weaknesses in the advances in knowledge in the social field, focused on diversity and intersectionality. There was a need to expand studies of an existential and clinical-epidemiological nature and of a health promotion trend, contemplating strategies that may contribute to the implementation of public policies and actions aimed at migrant women, in addition to empowerment actions on issues violence, and strengthening female autonomy, which can be made possible through cooperation and dialogue networks between university and society.